Pengaruh Inventarisasi Aset Tetap Daerah terhadap Kualitas Laporan Keuangan dengan Legal Audit sebagai Variabel Intervening - Imas Sukmawati; Endah Dwi Kusumastuti; Suji Abdullah Saleh (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to find out and evaluate the implementation of Regional Fixed Asset Inventory with audit activities that will impact the quality of financial statements. This research was conducted in the Bandung Regency Government using quantitative research methods with steps in this research namely by disseminating primary and secondary data (Questionnaire) in the form of The Examination Results Report (LHP) of BPK RI on the Financial Report of Bandung District Government in fiscal year 2015-2019. The research sample was selected by purposive sampling method which is the user of assets in 30 Government Agencies. With the expected data analysis results all variables have a positive effect. However, after data processing using SmartPLS software version 3.0 that the Inner Model test showed one of the three unproven hypotheses, among them the Legal Audit variable (Z) did not significantly affect the Financial Report Quality (Y) variable. However, in general the achievement of Regional Fixed Asset Inventory against Legal Audit and Implications on the Quality of Financial Statements is said to be good with one thing still to be improved and developed.